2011
DOI: 10.1002/bio.1293
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic electrochemiluminescence of the peroxydisulphate–ciprofloxacin system and its analytical applications

Abstract: The cathodic electrochemiluminescence (ECL) of peroxydisulphate (S(2)O(8)(2-))-ciprofloxacin (CPF) system at a wax-impregnated graphite electrode was studied. When CPF was absent, S(2)O(8)(2-) was electrochemically reduced to sulphate free radical (SO(4)(•-)), and dissolved oxygen absorbed on the electrode surface was reduced to protonated superoxide anion radical (HO(2)(•)). The HO(2)(•) was oxidized by SO(4)(•-) to produce molecular oxygen in both singlet and triplet states. Some of the singlet molecular oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…The HO 2 À could be further oxidized to a singlet molecular oxygen pair ( 1 O 2 ) 2 or an excited singlet molecular oxygen pair [ 1 (O 2 ) 2 ]*, and both ( 1 O 2 ) 2 and [ 1 (O 2 ) 2 ]* can produce weak ECL when converting to ground-state molecular oxygen. 32 At such a low cathodic potential (À2.5 V in this work), although the selfluminescence of K 2 S 2 O 8 brings somewhat ECL background, its signal intensity is at least an order of magnitude lower than that of Ce 2 Sn 2 O 7 . 26 Thus, the self-luminescence of K 2 S 2 O 8 is negligible compared to the stronger ECL of Ce 2 Sn 2 O 7 .…”
Section: Electrochemical Behavior Of Ecl Immunosensorsmentioning
confidence: 62%
“…The HO 2 À could be further oxidized to a singlet molecular oxygen pair ( 1 O 2 ) 2 or an excited singlet molecular oxygen pair [ 1 (O 2 ) 2 ]*, and both ( 1 O 2 ) 2 and [ 1 (O 2 ) 2 ]* can produce weak ECL when converting to ground-state molecular oxygen. 32 At such a low cathodic potential (À2.5 V in this work), although the selfluminescence of K 2 S 2 O 8 brings somewhat ECL background, its signal intensity is at least an order of magnitude lower than that of Ce 2 Sn 2 O 7 . 26 Thus, the self-luminescence of K 2 S 2 O 8 is negligible compared to the stronger ECL of Ce 2 Sn 2 O 7 .…”
Section: Electrochemical Behavior Of Ecl Immunosensorsmentioning
confidence: 62%
“…To date, there are two main mechanisms in the ECL system, one is ion annihilation ECL, the other is coreactant ECL . For the Ag NC modified the ITO electrode in the absence of S 2 O 8 2– , it was found that the ECL signal was too weak to be distinguished from that of bare ITO electrode, which implied that S 2 O 8 2– plays a crucial role as coreactant in the process of Ag NC ECL.…”
Section: Resultsmentioning
confidence: 99%
“…Many analytical techniques are being employed to determine CPX in different matrices, which include electrochemical, 9,10 immunoassay, 11 spectrofluorimetric, 12 capillary electrophoresis, 13 chemiluminescence, 14 spectrophotometry, 15,16 high-performance liquid chromatography 17 and liquid chromatography-mass spectroscopy 18 techniques. However, these analysis methods require expensive instrumentation, complex sample pretreatment, and preparation, which cannot meet large-scale actual testing.…”
Section: Introductionmentioning
confidence: 99%